Corporate Social Responsibility and Financial Performance an In-depth Analysis of Industry Variances - Hamdy, Karam Emad; Chyad, Azzam Khalid; Mahmood, Jateen Raoof; Abbas, Nazar Habeeb (Journal of Ecohumanism, 2024)
Background: Despite extensive research, the relationship between Corporate Social Responsibility (CSR) and financial success is still unclear. Variables specific to the industry might be significant in understanding these differences. This research examines the effect of CSR on financial performance in different sectors. Objective: The article aims to provide a thorough analysis of the impact of CSR programs on the financial performance of different companies. It aims to assess which sectors gain the most advantages from CSR initiatives and how industry variables impact this correlation. Methods: The study utilizes a combination of quantitative and qualitative analysis methods in a mixed-methods approach. Regression models were utilized to analyze financial data from 500 companies in ten sectors over a decade to assess the impact of CSR on financial results. Furthermore, case studies and interviews were conducted with industry professionals to gain a deeper insight into the operational mechanisms. Results: The findings show significant differences among industries in the relationship between CSR and financial performance. Industries that are highly visible to consumers, like retail and consumer goods, show a strong positive link between corporate social responsibility efforts and financial success. On the other hand, industries like heavy manufacturing, which have less interaction with consumers, demonstrate a less strong connection. Conclusion: The effect of CSR on economic performance differs depending on the industry. Increased visibility and interaction with customers enhance the advantages of CSR programs, suggesting that companies need to tailor their CSR approach to fit their specific industry. Managers and policymakers can use these discoveries to improve financial results through optimized CSR investments